HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP PENINGKATAN BERAT BADAN BALITA USIA 0-6 BULAN: HUBUNGAN PEMBERIAN ASI EKSKLUSIF TERHADAP PENINGKATAN BERAT BADAN BALITA USIA 0-6 BULAN - Fitriana, Alfira; Lianawati, Feni; Rahayu, Yustina (WELL BEING, 2022)
An increase in toddler weight is an increase that is quite likely to increase in weight every day. With the increase in toddler weight gain, toddlers should be given breast milk without other complementary foods, for example (PASI) at the age of 0-6 months. The purpose of this study was to determine the relationship of exclusive breastfeeding to the increase in body weight of toddlers aged 0-6 months. the method uses correlational analytics . The population of all mothers who have toddlers aged 0-6 months in Puton Village, Diwek District, Jombang Regency with a sample size of 55 toddlers with total sampling / saturated sample techniques. This study was measured using a questionnaire and analysed using the spearman rank correlation test. The results showed that all respondents experienced weight loss due to lack of breastfeeding, mothers thought that giving breast milk was unusual. From the results of the analysis obtained significant (sig) ρ value = 0.000, with (α) error rate (5% or 0.05) so (ρ < α = 0.05) this means H0 is rejected and H1 is accepted, with R = 0.945 which means there is a relationship between exclusive breastfeeding on increasing body weight of toddlers aged 0-6 months.